Pemodelan 2D Struktur Geologi Bawah Permukaan di Daerah Manifestasi Panas Bumi Buaran, Kabupaten Brebes, Berdasarkan Anomali Magnetik - Safrilia, Putri; Muhardi; Perdhana, Radhitya (JFT: Jurnal Fisika dan Terapannya, 2024)
Buaran Village is one of the villages in Brebes Regency that has a geothermal manifestation. This research aims to observe the subsurface geological structure of the Buaran geothermal manifestation area and its surroundings based on the distribution of magnetic anomalies. The digitization process was conducted on the Majenang sheet magnetic anomaly map published by the Geological Survey Centre which has made daily corrections and International Geomagnetic Reference Field (IGRF) corrections. The 2D modeling was performed on the residual magnetic anomaly obtained from the subtraction of the total magnetic anomaly from the reduction to the pole with the regional magnetic anomaly from the upward continuation. The distribution of residual magnetic anomalies obtained is -323.6 nT to 504.2 nT. Low anomalies are distributed in the northeast-southeast with values of -323.6 nT to -22.7 nT, while high anomalies are distributed in the north-south with values of 166.9 nT to 504.2 nT. 2D modeling results show subsurface geological structures in the form of fault structures, anticline folds, and syncline folds. Geothermal manifestations in the Buaran area are formed by the intrusion of igneous rocks as heat sources, and fault structures as hydrothermal fluid pathways.